Battery binder and preparation method thereof and lithium ion battery
By designing the composition of the battery adhesive and using specific components and controlling the proportion of components, the problem of unstable electrode structure of lithium-ion batteries in extreme environments is solved, and the battery's high capacity retention rate, good cycle performance and use safety are achieved.
Patent Information
- Application Number
- CN202211328138.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-27
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-10-27
AI Technical Summary
The adhesives in existing lithium-ion batteries are difficult to maintain the integrity of the electrode structure in extreme environments, resulting in a degradation of battery safety and cycling performance.
By designing the composition of the battery binder, using components such as isocyanate, aromatic diphenol or diamine, reactive long carbon chain polymer and acrylonitrile copolymer, the component ratio and reaction conditions are controlled to prepare a battery binder with low swelling rate and strong bonding ability.
The prepared lithium-ion battery has a small rebound after long-term charging and discharging, with high capacity retention, good cycle performance and safety of use.
Smart Images

Figure CN117996078B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of binders, and in particular relates to a battery binder and a preparation method thereof, and a lithium ion battery. Background Art
[0002] With the improvement of living standards, portable electronic devices and high-power electric vehicles have gradually become popular in people's daily life and work, and the demand for secondary batteries that provide energy and power for these devices has also increased. At the same time, the use environment of various devices has become increasingly complex, which has put forward higher requirements on the performance of secondary batteries. Obtaining secondary batteries with high energy density, high safety and high capacity retention rate is an important development direction for energy storage devices in the future.
[0003] As an important representative of secondary batteries, lithium-ion batteries are widely used due to their excellent characteristics of low self-discharge, good cycle performance and light weight. Among the many components of lithium-ion batteries, binders account for a relatively small proportion and are inactive components in the battery, but they connect active materials, conductive agents and current collectors into a whole, and play a vital role in ensuring that the pole pieces have good mechanical properties and processing performance, as well as maintaining the integrity of the conductive network during the battery's charge and discharge process.
[0004] At present, the most widely used binder in lithium-ion batteries is a fluorine-based resin represented by polyvinylidene fluoride (PVDF). However, for this fluorine-containing material, its raw material monomer belongs to fluorine-containing hydrocarbon compounds, which will damage the earth's ozone layer, so the production of PVDF is strictly controlled. In addition, the bonding force of PVDF mainly comes from the interfacial effect of weak van der Waals forces, which is difficult to effectively maintain the integrity of the electrode structure. In addition, it is easy to swell greatly in the electrolyte, and it is easy to peel off at the electrode interface during long-term circulation and high-temperature operation, causing electrode collapse and affecting battery safety. Therefore, PVDF has been difficult to adapt to the demand for binders in today's rapidly developing new energy technologies.
[0005] Therefore, how to provide an adhesive with a lower swelling rate and stronger bonding ability in the electrolyte, which can enable the battery to maintain a good electrode structure under extreme use environments, has become a technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a battery binder and a preparation method thereof and a lithium-ion battery. In the present invention, by designing the composition of the battery binder, the prepared battery binder has a low swelling rate and a strong bonding ability in the electrolyte, which can enable the battery to maintain a good electrode structure under extreme use environments. The lithium-ion battery prepared in this way has a small cell rebound after long-term charging and discharging, and has a high capacity retention rate, good cycle performance and safety in use. At the same time, the preparation method of the battery binder provided by the present invention is simple, the conditions are mild, and it is suitable for large-scale industrial production.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a battery binder, the battery binder comprising the following components in parts by weight: 70 to 90 parts of a first component and 10 to 30 parts of a second component;
[0009] The raw materials for preparing the first component include isocyanate, a first monomer and a second monomer;
[0010] The first monomer is selected from aromatic diphenols and / or aromatic diamines;
[0011] The second monomer is a reactive long carbon chain polymer;
[0012] The second component is an acrylonitrile copolymer.
[0013] In the present invention, by designing the composition of the battery binder, the prepared battery binder has a lower swelling rate and stronger bonding ability in the electrolyte, which can enable the battery to maintain a good electrode structure under extreme use environments. The lithium ion battery prepared in this way has a small cell rebound after long-term charge and discharge, and has a higher capacity retention rate, better cycle performance and safety in use.
[0014] In the present invention, by selecting aromatic diphenols and / or aromatic diamines as the first monomer, on the one hand, the battery binder provided by the present invention can have good mechanical properties, and on the other hand, since the aromatic ring is used as the main chain, the flexibility of the molecular chain can be reduced, and the molecular chain segments are more difficult to move, which can prevent the invasion of electrolyte, thereby obtaining a battery binder with better electrolyte resistance.
[0015] In the present invention, the reactive long carbon chain polymer refers to a long carbon chain polymer with a reactive end group (such as an amino group, a hydroxyl group, a carboxyl group, an epoxy group, etc.). The reactive long carbon chain polymer has a long carbon chain segment with a relatively small polarity, which has a small interaction with the electrolyte containing strong polar molecules and can effectively resist the intrusion of the electrolyte, thereby improving the electrolyte resistance of the battery binder. The reactive groups at both ends of the reactive long carbon chain polymer can ensure the chain growth ability of the polymer, which is beneficial to increase the molecular weight of the first component, increase the entanglement of the polymer chain, and hinder the intrusion of the electrolyte, thereby obtaining a battery binder with better electrolyte resistance.
[0016] In the present invention, the use of acrylonitrile copolymer can introduce cyano groups into the battery binder. The strong interaction between the cyano groups and the hydroxyl groups on the surface of the current collector further enhances the bonding performance between the battery binder and the current collector, which helps to maintain the stability of the battery's pole piece structure under extreme operating environments.
[0017] At the same time, the present invention controls the content of the first component and the second component within a specific range, so that the prepared battery binder has a lower swelling rate and stronger bonding ability. If the content of the second component is too much, the slurry viscosity of the prepared battery binder is unstable and may even gel; if the amount of the second component added is too little, the bonding force of the prepared battery binder is low. By adding the second component containing a binary or higher copolymer of acrylonitrile in the above proportion, the strong interaction between the cyano group in the acrylonitrile structure and the hydroxyl group on the surface of the current collector can be utilized to further enhance the bonding performance of the battery binder and the current collector, which helps to maintain the stability of the battery's pole piece structure under extreme use environments.
[0018] In the present invention, the weight proportion of the first component can be 70 parts, 72 parts, 74 parts, 76 parts, 78 parts, 80 parts, 82 parts, 84 parts, 86 parts, 88 parts or 90 parts, etc.
[0019] The weight proportions of the second component may be 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts or 30 parts, etc.
[0020] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0021] As a preferred technical solution of the present invention, the sum of the weight parts of the first component and the second component is 100 parts.
[0022] Preferably, the ratio of the mass of the isocyanate to the mass of the first monomer and the second monomer is (0.05-1.60):1.00, for example, it can be 0.05:1.00, 0.10:1.00, 0.20:1.00, 0.40:1.00, 0.60:1.00, 0.80:1.00, 1.00:1.00, 1.20:1.00, 1.40:1.00 or 1.60:1.00, etc.
[0023] Preferably, the mass ratio of the first monomer to the second monomer is (0.2-1.0):1.0, for example, it can be 0.2:1.0, 0.3:1.0, 0.4:1.0, 0.5:1.0, 0.6:1.0, 0.7:1.0, 0.8:1.0, 0.9:1.0 or 1.0:1.0, etc.
[0024] In the present invention, by controlling the mass ratio of the first monomer to the second monomer within a specific range, the prepared battery binder has a lower swelling rate and a stronger bonding ability. If the mass ratio of the first monomer to the second monomer is too small, that is, the content of the second monomer is too large, the glass transition temperature of the prepared battery binder is too low, which is not conducive to the subsequent electrode processing, and the stability of the prepared electrode structure is poor, and the safety of the long-term operation of the battery is poor; if the mass ratio of the first monomer to the second monomer is too large, that is, the content of the first monomer is too large, the glass transition temperature of the prepared battery binder is too high, the bonding force is low, and the prepared electrode becomes brittle, which is not conducive to battery circulation.
[0025] As a preferred technical solution of the present invention, the isocyanate is selected from aromatic isocyanate and / or aliphatic isocyanate.
[0026] Preferably, the aromatic isocyanate is selected from any one of 4,4′-diphenylmethane diisocyanate, 4,4′-diphenylmethane diisocyanate polymer, toluene diisocyanate, toluene diisocyanate polymer, xylene diisocyanate, dimethylbiphenyl diisocyanate, p-phenylene diisocyanate, 1,5-naphthalene diisocyanate or 3,3-dichlorobiphenyl-4,4-diisocyanate, or a combination of at least two thereof.
[0027] Preferably, the aliphatic isocyanate is selected from any one of tetramethylene diisocyanate, hexamethylene diisocyanate, dodecamethylene diisocyanate, trimethylhexamethylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate or lysine diisocyanate, or a combination of at least two thereof.
[0028] Preferably, the aromatic diphenol is selected from hydroquinone, resorcinol, bis(4-hydroxyphenyl)methane, bis(4-hydroxyphenyl)ether, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)sulfoxide, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl)ketone, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 2,2-bis(4-hydroxy-3,5 any one of 2,2-bis(4-hydroxy-3,5-dichlorophenyl)propane, 2,2-bis(4-hydroxy-3-bromophenyl)propane, 2,2-bis(4-hydroxy-3-chlorophenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane or bis(4-hydroxyphenyl)diphenylmethane, or a combination of at least two thereof.
[0029] Preferably, the aromatic diamine is selected from p-phenylenediamine, m-phenylenediamine, 3,5-diaminobenzoic acid, 4,4′-diaminodiphenyl ether, 3,4′-diaminodiphenyl ether, 4,4′-diaminobenzophenone, 4,4′-diaminodiphenyl sulfone, 3,3′-diaminodiphenyl sulfone, 4,4′-diaminobiphenyl, 4,4′-diaminodiphenylmethane, 4,4′-diamino-2,2′-dimethyl-1,1′-biphenyl, 4,4′-diaminobiphenyl Any one of benzene-2,2′-dicarboxylic acid, 3,3′,5,5′-tetramethylbenzidine, 4,4′-diaminooctafluorobiphenyl, 3,3-dichlorobenzidine, 2,7-diaminofluorene, 3,3′-dimethoxy-4,4′-diaminobiphenyl, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2′-bis(trifluoromethyl)diaminobiphenyl or 5-amino-2-(4-aminophenyl)benzimidazole, or a combination of at least two thereof.
[0030] In order to further reduce the swelling of the battery binder and improve the electrolyte resistance of the battery binder, an aromatic diphenol or an aromatic diamine with a smaller molecular weight may be further preferably used as the first monomer.
[0031] Preferably, the first monomer is selected from any one of hydroquinone, resorcinol, bis(4-hydroxyphenyl)methane, bis(4-hydroxyphenyl)ether, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)sulfoxide, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl)ketone, 1,1-bis(4-hydroxyphenyl)ethane, p-phenylenediamine, m-phenylenediamine, 3,5-diaminobenzoic acid, 4,4′-diaminodiphenyl ether, 3,4′-diaminodiphenyl ether, 4,4′-diaminobenzophenone, 4,4′-diaminodiphenyl sulfone, 3,3′-diaminodiphenyl sulfone, and 4,4′-diaminobiphenyl, or a combination of at least two thereof.
[0032] Preferably, the average molecular weight of the reactive long carbon chain polymer is 1000-10000, for example, 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000 or 10000.
[0033] Preferably, the concentration of reactive end groups in the reactive long carbon chain polymer is ≥200 mol / ton, for example, it can be 200 mol / ton, 250 mol / ton, 300 mol / ton, 350 mol / ton, 400 mol / ton, 450 mol / ton, 500 mol / ton, 550 mol / ton or 600 mol / ton, etc.
[0034] In order to improve the reactivity of the reactive long carbon chain polymer, it is preferred that the reactive long carbon chain polymer has a relatively small average molecular weight of less than or equal to 10,000 and a reactive end group (amino, hydroxyl, carboxyl, epoxy, etc.) concentration of ≥200 mol / ton.
[0035] Preferably, the reactive long carbon chain polymer includes any one or a combination of at least two of epoxy-terminated polybutadiene, amine-terminated polybutadiene, hydroxyl-terminated polybutadiene, hydroxyl-terminated polyacrylonitrile, amino-terminated butadiene-styrene copolymer, hydroxyl-terminated butadiene-styrene copolymer, carboxyl-terminated butadiene-acrylonitrile copolymer, amino-terminated butadiene-acrylonitrile copolymer, hydroxyl-terminated butadiene-acrylonitrile copolymer, epoxy-terminated butadiene-acrylonitrile copolymer or epoxy-terminated styrene-butadiene-styrene terblock copolymer.
[0036] As a preferred technical solution of the present invention, the acrylonitrile copolymer is selected from any one or a combination of at least two of styrene-acrylonitrile copolymer, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-methyl acrylate copolymer, acrylonitrile-acrylamide copolymer, methyl methacrylate-acrylonitrile copolymer, vinyl acetate-acrylonitrile copolymer or acrylonitrile-butadiene-styrene-acrylamide copolymer, and is further preferably any one or a combination of at least two of styrene-acrylonitrile copolymer, acrylonitrile-methyl acrylate copolymer, acrylonitrile-acrylamide copolymer and methyl methacrylate-acrylonitrile copolymer.
[0037] As a preferred technical solution of the present invention, the battery binder also includes a conductive material.
[0038] Preferably, the conductive material is selected from any one or a combination of at least two of conductive carbon black, conductive graphite, modified conductive graphite, metal particles, Ketjen black, carbon nanotubes, carbon fibers, graphene or conductive polymers.
[0039] In the present invention, the use of the conductive material can improve the conductivity of the battery binder in one step, improve the internal resistance of the battery, and enhance the performance of the battery cell.
[0040] Preferably, based on the sum of the weight parts of the first component and the second component as 100 parts, the mass part of the conductive material is 1 to 49 parts, for example, it can be 1 part, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts or 49 parts.
[0041] It should be noted that as long as the conductivity of the binder can be improved by compounding the conductive material, there are no special requirements for its compounding method and technical process. For example, the conductive material can be pretreated and then the binder polymer can be grafted onto the conductive material by chemical reaction. More specifically, carbon nanotubes can be acid-treated to obtain carboxylated carbon nanotubes, and then the binder polymer can be grafted onto the conductive material by chemical reaction between the active groups in the binder polymer and the carboxyl groups, so that the battery binder contains the conductive material.
[0042] As a preferred technical solution of the present invention, the dynamic viscosity of the battery binder is 10 2 ~10 5 mPa·s (for example, 10 2 mPa·s, 5×10 2 mPa·s, 10 3 mPa·s, 5×10 3 mPa·s, 10 4 mPa·s, 5×10 4 mPa·s or 10 5 mPa·s, preferably 10 3 ~10 4 mPa·s.
[0043] In the present invention, by controlling the dynamic viscosity of the battery binder within a specific range, the prepared battery binder has good uniformity. If the dynamic viscosity of the battery binder is too low, the prepared battery binder will have sedimentation behavior when preparing battery slurry (used for coating on the current collector to prepare electrode plates) in the subsequent preparation, and the coated plates will have poor uniformity; if the dynamic viscosity is too high, the prepared battery slurry is prone to local agglomeration and difficulty in dispersion, or the solid content of the battery slurry is too low, the amount of solvent used is increased, and the application cost is increased.
[0044] Preferably, the glass transition temperature of the battery binder is -20 to 150°C (for example, it may be -20°C, 0°C, 10°C, 20°C, 50°C, 70°C, 90°C, 100°C, 120°C, 140°C or 150°C, etc.), preferably 20 to 100°C.
[0045] In the present invention, the raw materials for preparing the battery binder are controlled to design the battery binder to have a suitable glass transition temperature, which is beneficial to improving the wetting ability of the binder on the surface of the current collector, thereby improving the adhesion. If the glass transition temperature of the battery binder is too low, the stability of the prepared electrode structure is likely to deteriorate, which is not conducive to the safety of long-term operation of the battery; if the peeling glass transition temperature of the battery binder is too high, the modulus of the prepared electrode plate is high, the brittleness increases, and the active material layer of the electrode plate is prone to powdering and falling off during the winding process, affecting the battery cell yield.
[0046] In a second aspect, the present invention provides a method for preparing the battery binder as described in the first aspect, the preparation method comprising the following steps:
[0047] (1) dissolving a first monomer in a solvent A to obtain a first monomer solution;
[0048] dissolving the second monomer in solvent B to obtain a second monomer solution;
[0049] (2) adding isocyanate to the second monomer solution obtained in step (1) to react and obtain a prepolymer solution;
[0050] (3) adding the first monomer solution obtained in step (1) to the prepolymer solution obtained in step (2) to react and obtain the first component;
[0051] (4) Mixing the first component and the second component to react, thereby obtaining the battery binder.
[0052] It should be noted that the isocyanate used in step (2) may be pure isocyanate or an isocyanate solution (obtained from the isocyanate solution solvent C), the mass concentration of the isocyanate solution is 1% to 100% (for example, it may be 1%, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or 99%, etc.), when the mass concentration of the cyanate solution is 100%, pure isocyanate is used;
[0053] The mass concentration of the first monomer solution is 1% to 50%, for example, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%.
[0054] The concentration of the second monomer solution is 1% to 50%, for example, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%.
[0055] As a preferred technical solution of the present invention, the solvent A and the solvent B are each independently selected from N-methylpyrrolidone and / or N,N-dimethylacetamide.
[0056] Preferably, the solvent C is selected from N-methylpyrrolidone and / or N,N-dimethylacetamide.
[0057] Preferably, the reaction temperature in step (2) is 50-80°C, for example, it can be 50°C, 52°C, 55°C, 57°C, 60°C, 63°C, 66°C, 68°C, 70°C, 72°C, 75°C, 77°C or 80°C, etc.
[0058] Preferably, the reaction time in step (2) is 60 to 360 min, for example, 60 min, 120 min, 180 min, 240 min, 300 min or 360 min.
[0059] Preferably, the reaction temperature in step (3) is 60-120°C, for example, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C.
[0060] Preferably, the reaction time in step (3) is 120 to 480 min, for example, 120 min, 180 min, 240 min, 300 min, 360 min, 420 min or 480 min.
[0061] It should be noted that the adding method described in step (2) and step (3) of the present invention is to add dropwise under stirring. In the present invention, there is no special requirement for the speed of adding dropwise. In the present invention, the isocyanate solution is added to the second monomer solution by gradually adding dropwise. If the dropping speed is large, the stirring speed of the dropping process can be increased. At the same time, in order to improve the reaction activity of the prepolymer obtained in the second step, so that the prepolymer can better participate in the next reaction and more easily obtain a battery binder with suitable viscosity, the concentration of isocyanate groups as the ends of the molecular chains in the prepolymer can be further increased. In the present invention, the mass concentration of isocyanate groups as the ends of the molecular chains in the prepolymer is ≥1.5%, for example, it can be 1.5%, 2%, 3%, 4%, 6%, 8%, 10% or 12%. The concentration of the isocyanate groups can be obtained by testing using ASTM D2572.
[0062] It should be noted that, in order to further increase the molecular weight and improve the electrolyte resistance of the battery binder, an organic small molecule chain extender can be added during the reaction of step (3), and the mass percentage of the organic small molecule chain extender is 0.5% to 5.0%, for example, 0.5%, 1.0%, 2.0%, 3.0%, 4.0% or 5%, etc., based on the total mass of the solid in the first component (the mass sum of the isocyanate, the first monomer and the second monomer) as 100%. The present invention does not have any special restrictions on the type of organic small molecule chain extender, and all organic small molecule chain extenders that can react with isocyanate groups are applicable. From the perspective of further reducing the swelling rate of the battery binder and improving the electrolyte resistance of the battery binder, the organic small molecule chain extender is preferably a dibasic acid anhydride chain extender, which exemplarily includes but is not limited to: any one or a combination of at least two of pyromellitic anhydride, biphenyl tetracarboxylic anhydride, diphenyl ether tetracarboxylic anhydride, and dibenzophenone tetracarboxylic anhydride.
[0063] In a third aspect, the present invention provides a battery pole piece, wherein the battery pole piece comprises the battery adhesive as described in the first aspect.
[0064] Preferably, the battery electrode is a positive electrode or a negative electrode.
[0065] When the battery binder provided by the present invention is applied to battery pole pieces, there is no special restriction on the manufacturing process of the battery pole pieces, which exemplarily includes but is not limited to: wet, semi-dry or dry batching process, wherein materials such as battery binder, active material, conductive agent and solvent are uniformly mixed to prepare electrode slurry, and then the slurry is uniformly coated on the current collector by a coater, and then the battery pole pieces are obtained through drying, calendering, slitting and other processes.
[0066] It should be noted that since the battery binder provided by the present invention has good electrolyte resistance and excellent performance stability in the electrolyte, the battery binder provided by the present invention can be applied to the positive electrode material of the battery in practical applications. At the same time, it can also be applied to other application fields that come into contact with the electrolyte, for example, the edge of the positive electrode, the bottom of the positive electrode, the negative electrode material, the edge of the negative electrode, the bottom of the negative electrode and the separator.
[0067] When the battery binder provided by the present invention is applied to the positive electrode sheet and the negative electrode sheet of the battery, there is no special limitation on the type of active material selected in the positive electrode sheet or the negative electrode sheet, and there is no special limitation on the particle size of the active material. Regarding the positive electrode active material used, it exemplarily includes but is not limited to: lithium iron phosphorus oxide, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium iron oxide, lithium nickel manganese oxide, lithium cobalt nickel oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and any one or more combinations of their composites; Regarding the negative electrode active material used, it exemplarily includes but is not limited to: any one or a combination of at least two of carbon / silicon materials, metals and metal oxides; the carbon / silicon material is selected from any one or a combination of at least two of natural graphite, artificial graphite, amorphous carbon, diamond-like carbon, carbon nanotubes, carbon / silicon hybrid materials, silicon oxide, silicon; the metal exemplarily includes but is not limited to: one or a metal alloy of at least two of lithium, aluminum, tin, silver, zinc, calcium, barium, mercury, platinum, technetium, bismuth, indium; the metal oxide exemplarily includes but is not limited to: one or a combination of at least two of aluminum oxide, tin oxide, indium oxide, zinc oxide, lithium oxide.
[0068] In a fourth aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the battery electrode sheet as described in the third aspect.
[0069] Compared with the prior art, the present invention has the following beneficial effects:
[0070] In the present invention, the components of the battery binder are designed, and the contents of the first component and the second component are controlled within a specific range, and the mass ratio of the first monomer to the second monomer in the first component is controlled within a specific range. The prepared battery binder has suitable dynamic viscosity and glass transition temperature, and has strong bonding strength and electrical properties. The pole piece prepared in this way can maintain good integrity after being immersed in electrode liquid at 70° C. for 7 days, and the pole piece surface will not fall off or crack in a large area. The peel strength is 0.8-9.5 N / m. The first charge and discharge efficiency of the lithium ion battery prepared in this way is greater than 90%, specifically 91.7-94.2%, and the capacity retention rate after 500 cycles is 87.2-94.5%. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] Figure 1 This is a graph showing the test results of a pole piece prepared by the battery binder provided in Example 1 of the present invention after the pole piece electrolyte resistance performance test is carried out;
[0072] Figure 2 A graph representing the test results of a pole piece prepared by the battery binder provided in Example 11 of the present invention after the pole piece electrolyte resistance performance test is carried out;
[0073] Figure 3 This is a characterization diagram of the test results of the electrode prepared by the battery binder provided in Comparative Example 6 of the present invention after the electrode piece electrolyte resistance performance test was carried out. DETAILED DESCRIPTION
[0074] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0075] It should be noted that the components used in the following examples and comparative examples are all commercially available products and can be purchased.
[0076] Some components in the embodiments and comparative examples are described as follows:
[0077] 4,4′-diphenylmethane diisocyanate polymer: the mass content of isocyanate group is 30%;
[0078] Toluene diisocyanate polymer: the mass content of isocyanate group is 30%;
[0079] Epoxy-terminated butadiene-acrylonitrile copolymer 1: the epoxy content is 600 mol / ton, and the mass content of cyano group is 15%;
[0080] Epoxy-terminated butadiene-acrylonitrile copolymer 2: the epoxy group content is 400 mol / ton, and the mass content of cyano group is 15%;
[0081] Epoxy-terminated butadiene-acrylonitrile copolymer 3: the epoxy content is 150 mol / ton, and the mass content of cyano group is 15%;
[0082] Terminal hydroxyl butadiene-styrene copolymer; hydroxyl content is 200 mol / ton, and phenyl mass content is 15%;
[0083] Amino-terminated butadiene-acrylonitrile copolymer: the amino content is 600 mol / ton, and the mass content of cyano group is 15%;
[0084] Hydroxyl-terminated polyacrylonitrile: hydroxyl content is 600 mol / ton, and cyano content is 53% by mass;
[0085] Amino-terminated styrene-butadiene-styrene terpolymer: the amino content is 600 mol / ton, and the mass content of phenyl is 15%;
[0086] Carboxyl-terminated butadiene-styrene copolymer: carboxyl content is 600 mol / ton, and the mass content of phenyl is 15%;
[0087] Acrylonitrile-acrylamide copolymer: the mass average molecular weight is 150,000 to 200,000, and the mass content of cyano group is 15%;
[0088] Methyl methacrylate-acrylonitrile copolymer: the mass average molecular weight is 150,000 to 200,000, and the mass content of cyano group is 15%;
[0089] Styrene-acrylonitrile copolymer: the mass average molecular weight is 150,000 to 200,000, and the mass content of cyano group is 15%;
[0090] Acrylonitrile-methyl acrylate copolymer: the mass average molecular weight is 150,000-200,000, and the mass content of cyano group is 15%.
[0091] Example 1
[0092] This embodiment provides a battery binder, the battery binder comprising the following components in parts by weight: a first component and a second component;
[0093] The raw materials for preparing the first component include 263g of 4,4′-diphenylmethane diisocyanate polymer, 98g of hydroquinone and 359g of epoxy-terminated butadiene-acrylonitrile copolymer 1 (epoxy content of 600 mol / ton);
[0094] The second component is 180 g of acrylonitrile-acrylamide copolymer.
[0095] The preparation method of the above battery binder is as follows:
[0096] (1) dissolving 263 g of 4,4′-diphenylmethane diisocyanate polymer in 789 g of N-methylpyrrolidone to obtain an isocyanate solution;
[0097] Dissolving 98 g of hydroquinone in 294 g of N-methylpyrrolidone to obtain a first monomer solution;
[0098] Dissolving 359 g of epoxy-terminated butadiene-acrylonitrile copolymer 1 (epoxy content: 600 mol / ton) in 1077 g of N-methylpyrrolidone to obtain a second monomer solution;
[0099] (2) adding the second monomer solution obtained in step (1) into a 10L glass reactor equipped with a polytetrafluoroethylene stirring paddle, adjusting the reactor temperature to 80°C and the stirring speed to 400 r / min, adding the isocyanate solution prepared in step 1 into the reactor through a peristaltic pump, and completing the addition within 60 min, and then reacting at a constant temperature for 300 min to obtain a prepolymer solution;
[0100] (3) adjusting the temperature of the reactor to 90° C. and the stirring speed to 400 r / min, adding the first monomer solution obtained in step (1) into the reactor through a peristaltic pump, and completing the addition within 60 min, and then reacting at a constant temperature for 300 min to obtain the first component.
[0101] (4) 180 g of acrylonitrile-acrylamide copolymer was added to the reaction kettle and mixed and reacted at 60° C. for 60 min, and N-methylpyrrolidone was added to adjust the solid content to 10% to obtain the battery binder.
[0102] Example 2
[0103] This embodiment provides a battery binder, which is different from Embodiment 1 only in that the 4,4′-diphenylmethane diisocyanate polymer is replaced by 4,4′-diphenylmethane diisocyanate, and the terminal epoxy butadiene-acrylonitrile copolymer 1 is replaced by the terminal amino butadiene-acrylonitrile copolymer, and other conditions are the same as those in Embodiment 1.
[0104] Example 3
[0105] This embodiment provides a battery binder, which is different from Example 1 only in that 263g of 4,4′-diphenylmethane diisocyanate polymer is replaced by 263g of 4,4′-diphenylmethane diisocyanate, 98g of hydroquinone is replaced by 103g of hydroquinone, and 180g of acrylonitrile-acrylamide copolymer is replaced by 206g of acrylonitrile-acrylamide copolymer. Other conditions are the same as those in Example 1.
[0106] Example 4
[0107] This embodiment provides a battery binder, which is different from the embodiment 1 only in that hydroquinone is replaced by p-phenylenediamine, the reaction temperature of step (3) is 60° C., and other conditions are the same as those of the embodiment 1.
[0108] Example 5
[0109] This embodiment provides a battery binder, which is different from Embodiment 1 only in that the epoxy-terminated butadiene-acrylonitrile copolymer 1 is replaced by hydroxy-terminated polyacrylonitrile, and the acrylonitrile-acrylamide copolymer is replaced by methyl methacrylate-acrylonitrile copolymer, and other conditions are the same as those in Embodiment 1.
[0110] Example 6
[0111] This embodiment provides a battery binder, which is different from Example 1 only in that hydroquinone is replaced by 3,5-diaminobenzoic acid, and the terminal epoxy butadiene-acrylonitrile copolymer 1 (epoxy content is 600 mol / ton) is replaced by the terminal epoxy butadiene-acrylonitrile copolymer 2 (epoxy content is 400 mol / ton), and other conditions are the same as Example 1.
[0112] Example 7
[0113] This embodiment provides a battery binder, which is different from Example 1 only in that 4,4′-diphenylmethane diisocyanate polymer is replaced by toluene diisocyanate polymer, and the epoxy-terminated butadiene-acrylonitrile copolymer 1 is replaced by an amino-terminated styrene-butadiene-styrene terpolymer, and other conditions are the same as Example 1.
[0114] Example 8
[0115] This embodiment provides a battery binder, which is different from Example 1 only in that 4,4′-diphenylmethane diisocyanate polymer is replaced by toluene diisocyanate, hydroquinone is replaced by bis-(4-hydroxybenzene) sulfide, and acrylonitrile-acrylamide copolymer is replaced by styrene-acrylonitrile copolymer, and other conditions are the same as those in Example 1.
[0116] Example 9
[0117] This embodiment provides a battery binder, which is different from the embodiment 1 only in that 4,4′-diphenylmethane diisocyanate polymer is replaced by toluene diisocyanate polymer, and hydroquinone is replaced by 4,4′-diaminobenzophenone, and other conditions are the same as those in the embodiment 1.
[0118] Example 10
[0119] This embodiment provides a battery binder, which is different from Example 1 only in that hydroquinone is replaced by p-phenylenediamine, and the terminal epoxy butadiene-acrylonitrile copolymer 1 is replaced by a terminal hydroxyl butadiene-styrene copolymer 3 (with a hydroxyl content of 200 mol / ton), and other conditions are the same as those in Example 1.
[0120] Embodiment 11
[0121] This embodiment provides a battery binder, which is different from Example 1 only in that hydroquinone is replaced by 4,4′-diaminodiphenylmethane, the terminal epoxy butadiene-acrylonitrile copolymer 1 is replaced by a terminal carboxyl butadiene-styrene copolymer, and 180g of acrylonitrile-acrylamide copolymer is replaced by 308g of methyl methacrylate-acrylonitrile copolymer. Other conditions are the same as those in Example 1.
[0122] Example 12
[0123] This embodiment provides a battery binder, which is different from Embodiment 1 only in that hydroquinone is replaced by 4,4′-diaminodiphenyl ether, and 180 g of acrylonitrile-acrylamide copolymer is replaced by 80 g of acrylonitrile-methyl acrylate copolymer, and other conditions are the same as those in Embodiment 1.
[0124] Example 13
[0125] This embodiment provides a battery binder, which is different from the embodiment 1 only in that the content of acrylonitrile-acrylamide copolymer in the battery binder is 308 g, and other conditions are the same as those in the embodiment 1.
[0126] Embodiment 14
[0127] This embodiment provides a battery binder, which is different from the embodiment 1 only in that the content of acrylonitrile-acrylamide copolymer in the battery binder is 80 g, and other conditions are the same as those in the embodiment 1.
[0128] Embodiment 15
[0129] This embodiment provides a method which is different from Embodiment 1 only in that, in the first component, the content of hydroquinone is 72 g, and other conditions are the same as those in Embodiment 1.
[0130] Example 16
[0131] This embodiment provides a battery binder, which is different from the embodiment 1 only in that, in the first component, the content of the epoxy-terminated butadiene-acrylonitrile copolymer 1 is 98 g, and other conditions are the same as those in the embodiment 1.
[0132] Embodiment 17
[0133] This embodiment provides a battery binder, which is different from the embodiment 1 only in that the battery binder further includes 150 g of conductive carbon black, and other conditions are the same as those of the embodiment 1.
[0134] Embodiment 18
[0135] This comparative example provides a battery binder, which is different from Example 1 only in that the epoxy-terminated butadiene-acrylonitrile copolymer 1 (epoxy content of 600 mol / ton) is replaced by the epoxy-terminated butadiene-acrylonitrile copolymer 3 (epoxy content of 150 mol / ton), and other conditions are the same as those in Example 1.
[0136] Embodiment 19
[0137] This comparative example provides a battery binder, which is different from Example 1 only in that 4,4′-diphenylmethane diisocyanate polymer is replaced by toluene diisocyanate polymer, and hydroquinone is replaced by 2,2-bis[4-(4-aminophenoxy)phenyl]propane, and other conditions are the same as Example 1.
[0138] Embodiment 20
[0139] This embodiment provides a battery binder, which is different from the embodiment 1 only in that the addition amount of hydroquinone is adjusted to 106 g, the addition amount of the epoxy-terminated butadiene-acrylonitrile copolymer 1 is adjusted to 106 g, and the other implementation conditions are the same as those of the embodiment 1.
[0140] Comparative Example 1
[0141] This comparative example provides a battery binder, which is different from Example 1 only in that the content of acrylonitrile-acrylamide copolymer in the battery binder is 480 g, and other conditions are the same as those in Example 1.
[0142] Comparative Example 2
[0143] This comparative example provides a battery binder, which is different from Example 1 only in that the content of acrylonitrile-acrylamide copolymer in the battery binder is 50 g, and other conditions are the same as those in Example 1.
[0144] Comparative Example 3
[0145] This comparative example provides a method which is different from Example 1 only in that the content of hydroquinone in the first component is 40 g, and other conditions are the same as those in Example 1.
[0146] Comparative Example 4
[0147] This comparative example provides a battery binder, which is different from Example 1 only in that, in the first component, the content of the epoxy-terminated butadiene-acrylonitrile copolymer 1 is 70 g, and other conditions are the same as those in Example 1.
[0148] Comparative Example 5
[0149] This comparative example provides a battery binder, which is different from Example 1 only in that hydroquinone is replaced by 1,4-bis(2-hydroxyethyl)benzene, and other conditions are the same as those in Example 1.
[0150] Comparative Example 6
[0151] This comparative example provides a battery binder, which is different from Example 1 only in that the amount of hydroquinone used in the preparation raw materials of the first component is 110 g, and the preparation raw materials of the first component do not contain terminal epoxy butadiene-acrylonitrile copolymer 1, and other conditions are the same as Example 1.
[0152] Comparative Example 7
[0153] This comparative example provides a battery binder, which is PVDF produced by French company Arkema, with a model of KYNAR HSV 900.
[0154] The battery binder prepared in Examples 1 to 19 and Comparative Examples 1 to 7 was added to the battery pole sheet formula to prepare the pole sheet by the following method:
[0155] In parts by weight, 95 parts of lithium iron phosphate (Defang Nano, model DY-3), 2.5 parts of conductive carbon black Super P and 2.5 parts of battery binder were added to N-methylpyrrolidone at a total solid content of 65%, and mixed using a double planetary mixer to obtain an electrode slurry containing the prepared battery binder. The uniformly dispersed slurry was filtered through a 100-mesh screen, coated on a 10 μm thick aluminum foil by an extrusion coater, dried in a 110°C forced air drying oven, and then heated to 1×10 4 The positive electrode sheet is obtained by rolling with a unit length load of N / m.
[0156] The test methods for the above battery binders and the pole pieces prepared by the battery binders are as follows:
[0157] Glass transition temperature test: measured using MDSC2910 differential scanning calorimeter (DSC) from TA Corporation of the United States;
[0158] Dynamic viscosity test: The dynamic viscosity was measured using the NDJ-8S digital rotational viscometer produced by Shanghai Fangrui Instrument Co., Ltd.
[0159] Electrode piece electrolyte resistance test: The prepared electrode piece was cut into 700mm×50mm strips, immersed in the prepared electrolyte (ethylene carbonate: dimethyl carbonate: diethyl carbonate = 1:1:1 (mass ratio), LiPF6 concentration is 1.0M) at 70°C, sealed and stored for 7 days, and then taken out to observe the surface status of the electrode piece: the electrode piece is intact and marked as ○, the electrode piece film layer is partially detached and marked as □, and large-area detachment or large-area cracking is marked as ×.
[0160] Pole piece peeling force test: The electrode piece soaked in the electrolyte was cut into 100mm×20mm strips, the current collector side was fixed to a 1mm thick steel plate with double-sided tape, and a transparent tape was pasted on the coating layer side. At 25°C, a 180° pulling peeling test was performed with a universal electronic testing machine at a peeling speed of 100mm / min, and the peeling stress was recorded;
[0161] Battery performance test: Use the pole piece to make a 1.2Ah soft pack battery cell, test its initial charge and discharge efficiency and perform a cycle performance test. The test steps are as follows:
[0162] (1) The soft-pack battery prepared above was formed and divided into different capacities at 25° C. using a battery test cabinet, wherein:
[0163] Formation step: charge at 0.05C constant current for 2.0h, then charge at 0.15C constant current for 2.5h;
[0164] Capacity division step: charge to 3.7V at a constant current of 0.33C, then charge to a cut-off current of 0.02C at a constant voltage of 3.7V, and discharge to 2V at 0.33C. Record the total amount of electricity charged in the formation step and the capacity division step and the discharge capacity after discharge;
[0165] Initial charge and discharge efficiency (%) = discharge capacity after capacity-divided discharge / total amount of electricity charged after formation and capacity-divided discharge;
[0166] Capacity retention rate after 500 cycles: At 25°C, charge the battery after capacity division at a constant current of 0.33C to 3.7V, then charge it at a constant voltage to a cut-off current of 0.02C, leave it for 5 minutes, discharge it at 0.33C to 2V, leave it for 5 minutes, and record the discharge capacity after the first charge and discharge;
[0167] Charge to 3.7V at 0.5C constant current, then charge to a cut-off current of 0.02C at constant voltage, leave for 5 min, discharge to 2V at 0.5C, leave for 5 min, repeat this cycle, charge / discharge 500 times, and record the discharge capacity after the 500th cycle;
[0168] The capacity retention rate of the battery after 500 cycles was calculated using the following formula: Capacity retention rate after 500 cycles (%) = discharge capacity after the 500th cycle / discharge capacity after the first cycle.
[0169] The performance test results of the above battery binders and the pole pieces prepared by the battery binders are shown in Table 1.
[0170] Table 1
[0171]
[0172]
[0173] It can be seen from the data in Table 1 that in the present invention, by designing the components of the battery binder, controlling the contents of the first component and the second component within a specific range, and controlling the mass ratio of the first monomer to the second monomer in the first component within a specific range, the prepared battery binder has suitable dynamic viscosity and glass transition temperature, and has strong bonding strength and electrical properties. The pole piece prepared in this way can maintain good integrity after being immersed in the electrode liquid at 70°C for 7 days, and the pole piece surface will not fall off or crack in a large area. The peel strength is 0.8-9.5N / m. The initial charge and discharge efficiency of the lithium ion battery prepared in this way is greater than 90%, specifically 91.7-94.2%, and the capacity retention rate after 500 cycles is 87.2-94.5%.
[0174] The test results of the electrolyte resistance performance of the pole pieces prepared by the battery binders provided in Example 1, Example 11 and Comparative Example 6 are as follows: Figure 1-3 As shown by Figure 1-3 It can be seen that the battery binder prepared by designing the components of the battery binder in the present invention (Example 1, Example 11) has strong bonding performance, and the pole piece prepared thereby has good electrolyte resistance. After being immersed in an electrolyte at 70°C for 7 days, the surface of the pole piece can basically remain intact without large-scale shedding; if the first component does not contain the second monomer (Comparative Example 6, Figure 3 ), the prepared electrode had poor electrolyte resistance. After being immersed in an electrolyte at 70°C for 7 days, a large area of the electrode fell off.
[0175] Compared with Example 1, if the concentration of the reactive end groups in the second monomer is too low (Example 18), the performance of the prepared battery binder is poor, and the pole piece prepared thereby has poor peeling strength after being immersed in the electrolyte, resulting in large-scale shedding.
[0176] Compared with Example 1, if the content of the first component is too little (Comparative Example 1) or too much (Comparative Example 2), the prepared battery binder has poor electrolyte resistance and peel strength properties.
[0177] Compared with Example 1, if the mass ratio of the first monomer to the second monomer in the preparation raw materials of the first component is too small (Comparative Example 3) or the mass ratio of the first monomer to the second monomer is too large (Comparative Example 4), the performance of the prepared battery binder is also poor, and the electrical performance of the lithium-ion battery prepared thereby is poor.
[0178] Compared with Example 1, if an aromatic diol is selected as the first monomer (Comparative Example 5), the performance of the prepared battery binder is poor, and the electrical performance of the lithium-ion battery prepared therefrom is also poor; if the preparation raw materials of the first component do not contain the second monomer (Comparative Example 6), the performance of the prepared battery binder is poor; if a commercially available battery binder is selected (Comparative Example 7), its adhesion is poor.
[0179] In summary, in the present invention, by designing the components of the battery binder, controlling the contents of the first component and the second component within a specific range, and controlling the mass ratio of the first monomer to the second monomer in the first component within a specific range, the prepared battery binder has suitable dynamic viscosity and glass transition temperature, as well as strong bonding strength and electrical properties.
[0180] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A battery adhesive, characterized in that: The battery binder comprises the following components in parts by weight: 70-90 parts of a first component and 10-30 parts of a second component; The raw materials for preparing the first component include isocyanate, a first monomer and a second monomer; The first monomer is selected from aromatic diphenols and / or aromatic diamines; The second monomer is a reactive long carbon chain polymer; The second component is an acrylonitrile copolymer; The mass ratio of the first monomer to the second monomer is (0.2~1.0):1.
0.
2. The battery binder according to claim 1, characterized in that: The sum of the weight parts of the first component and the second component is 100 parts.
3. The battery binder according to claim 1, characterized in that: The ratio of the mass of the isocyanate to the sum of the mass of the first monomer and the second monomer is (0.05-1.60):1.
00.
4. The battery binder according to claim 1, characterized in that: The isocyanate is selected from aromatic isocyanates and / or aliphatic isocyanates.
5. The battery binder according to claim 4, characterized in that: The aromatic isocyanate is selected from any one of 4,4′-diphenylmethane diisocyanate, 4,4′-diphenylmethane diisocyanate polymer, toluene diisocyanate, toluene diisocyanate polymer, xylene diisocyanate, dimethylbiphenyl diisocyanate, p-phenylene diisocyanate, 1,5-naphthalene diisocyanate or 3,3-dichlorobiphenyl-4,4-diisocyanate, or a combination of at least two thereof.
6. The battery binder according to claim 4, characterized in that: The aliphatic isocyanate is selected from any one of tetramethylene diisocyanate, hexamethylene diisocyanate, dodecamethylene diisocyanate, trimethylhexamethylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate or lysine diisocyanate, or a combination of at least two thereof.
7. The battery binder according to claim 1, characterized in that: The aromatic diphenol is selected from hydroquinone, resorcinol, bis(4-hydroxyphenyl)methane, bis(4-hydroxyphenyl)ether, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)sulfoxide, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl)ketone, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 2,2-bis(4-hydroxy-3,5-dihydroxyphenyl)propane, any one of bis(4-hydroxyphenyl)-1-phenylethane or bis(4-hydroxyphenyl)diphenylmethane, or a combination of at least two thereof.
8. The battery binder according to claim 1, characterized in that: The aromatic diamine is selected from p-phenylenediamine, m-phenylenediamine, 3,5-diaminobenzoic acid, 4,4′-diaminodiphenyl ether, 3,4′-diaminodiphenyl ether, 4,4′-diaminobenzophenone, 4,4′-diaminodiphenyl sulfone, 3,3′-diaminodiphenyl sulfone, 4,4′-diaminobiphenyl, 4,4′-diaminodiphenylmethane, 4,4′-diamino-2,2′-dimethyl-1,1′-biphenyl, 4,4′-diaminobiphenyl- Any one of 2,2′-dicarboxylic acid, 3,3′,5,5′-tetramethylbenzidine, 4,4′-diaminooctafluorobiphenyl, 3,3-dichlorobenzidine, 2,7-diaminofluorene, 3,3′-dimethoxy-4,4′-diaminobiphenyl, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2′-bis(trifluoromethyl)diaminobiphenyl or 5-amino-2-(4-aminophenyl)benzimidazole, or a combination of at least two thereof.
9. The battery binder according to claim 1, characterized in that: The average molecular weight of the reactive long carbon chain polymer is 1000-10000.
10. The battery binder according to claim 1, characterized in that: The concentration of reactive end groups in the reactive long carbon chain polymer is ≥200 mol / ton.
11. The battery binder according to claim 1, characterized in that: The reactive long carbon chain polymer includes any one of epoxy-terminated polybutadiene, amine-terminated polybutadiene, hydroxyl-terminated polybutadiene, hydroxyl-terminated polyacrylonitrile, amino-terminated butadiene-styrene copolymer, hydroxyl-terminated butadiene-styrene copolymer, carboxyl-terminated butadiene-acrylonitrile copolymer, amino-terminated butadiene-acrylonitrile copolymer, hydroxyl-terminated butadiene-acrylonitrile copolymer, epoxy-terminated butadiene-acrylonitrile copolymer or epoxy-terminated styrene-butadiene-styrene terblock copolymer or a combination of at least two thereof.
12. The battery binder according to claim 1, characterized in that: The acrylonitrile copolymer is selected from any one of styrene-acrylonitrile copolymer, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-methyl acrylate copolymer, acrylonitrile-acrylamide copolymer, methyl methacrylate-acrylonitrile copolymer, vinyl acetate-acrylonitrile copolymer or acrylonitrile-butadiene-styrene-acrylamide copolymer or a combination of at least two thereof.
13. The battery binder according to claim 12, characterized in that: The acrylonitrile copolymer is selected from any one of styrene-acrylonitrile copolymer, acrylonitrile-methyl acrylate copolymer, acrylonitrile-acrylamide copolymer, methyl methacrylate-acrylonitrile copolymer or a combination of at least two thereof.
14. The battery binder according to claim 1, characterized in that: The battery binder also includes a conductive material.
15. The battery binder according to claim 14, characterized in that: The conductive material is selected from any one or a combination of at least two of conductive carbon black, conductive graphite, modified conductive graphite, metal particles, Ketjen black, carbon nanotubes, carbon fibers, graphene or conductive polymers.
16. The battery binder according to claim 14, characterized in that: Based on 100 parts by weight of the sum of the first component and the second component, the mass fraction of the conductive material is 1 to 49 parts.
17. The battery binder according to claim 1, characterized in that: The dynamic viscosity of the battery binder is 10 2 ~10 5 mPa·s.
18. The battery adhesive according to claim 17, characterized in that: The dynamic viscosity of the battery binder is 10 3 ~10 4 mPa·s.
19. The battery binder according to claim 1, characterized in that: The glass transition temperature of the battery binder is -20 to 150°C.
20. The battery binder according to claim 19, characterized in that The glass transition temperature of the battery binder is 20-100°C.
21. A method for preparing a battery binder according to any one of claims 1 to 20, characterized in that: The preparation method comprises the following steps: (1) dissolving a first monomer in a solvent A to obtain a first monomer solution; dissolving the second monomer in solvent B to obtain a second monomer solution; (2) adding isocyanate to the second monomer solution obtained in step (1) to react and obtain a prepolymer solution; (3) adding the first monomer solution obtained in step (1) to the prepolymer solution obtained in step (2) to react and obtain the first component; (4) The first component and the second component are mixed and reacted to obtain the battery binder.
22. The preparation method according to claim 21, characterized in that: The solvent A and solvent B are each independently selected from N -methylpyrrolidone and / or N,N -Dimethylacetamide.
23. The preparation method according to claim 21, characterized in that: The reaction temperature in step (2) is 50-80°C.
24. The preparation method according to claim 21, characterized in that: The reaction time in step (2) is 60 to 360 min.
25. The preparation method according to claim 21, characterized in that: The reaction temperature in step (3) is 60-120°C.
26. The preparation method according to claim 21, characterized in that: The reaction time in step (3) is 120 to 480 min.
27. A battery pole piece, characterized in that: The battery pole piece includes the battery adhesive as described in any one of claims 1-20.
28. The battery pole piece according to claim 27, characterized in that: The battery electrode is a positive electrode or a negative electrode.
29. A lithium ion battery, characterized in that: The lithium-ion battery comprises the battery pole piece as claimed in claim 27 or 28.
Citation Information
Patent Citations
Epoxy / elastomer adduct, method of forming same and materials and articles formed therewith
US20040204551A1
Electrically conductive one component (1K) epoxy formulation
WO2022043160A1